PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN GRABFOOD (STUDI PADA MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI TULUNGAGUNG) - Prayogo, Gayuh; Sunaryo, Agus; Umami, Nailariza (Relawan Jurnal Indonesia, 2025)
This study aimed to determine how Bhinneka PGRI University Tulungagung's Grabfood purchasing decisions were influenced by promotion and service quality students enrolled in the Economic Education Study Program. This study employs a questionnaire and is quantitative in nature. 167 Bhinneka PGRI University Economics Education students who utilized Grabfood participated in this study. using the Nonprobability the Purposive Sampling Technique type of sampling technique. This study used SPSS 20 software. The equation Y = 3.017 + 0.426X1 + 0.653X2 was found from the multiple linear regression results. These two Several factors significantly influence Grabfood customers' decisions to buy.partially; variable (X1) promotion tcount 4.325 is greater than ttable 1.974, and variable (X2) service quality tcount 8.007 is greater than ttable 1.974. In addition, simultaneously, the two variables have a significant impact, with an Fcount of 96.129 greater than the Ftable 3.90. The two variables account for 53.4% of the variation in purchase decisions, with an adjusted R square of 0.534, while other factors account for 46.6%. Given that enhancing service quality (X2) influences decisions to buy more than promotion (X1), which has a regression coefficient of 0.426, Grabfood should prioritize it.